Alternatives for connecting GPS observations to the conventional basic geodetic control in Venezuela - Acuña, Gustavo; Hoyer, Melvin; Wildermann, Eugen (Rev. Téc. Fac. Ing. Univ. Zulia)
A study of alternatives for connecting GPS observations to the conventional basic geodetic control, regularly used in Venezuela, is performed. Each technique and its respective variants are considered for their application pertinence and quality analyzing and comparing results from a test network. Finally, an optimized method to the new Venezuelan GPS network referred to the geocentric reference system of South America is presented.